1971
DOI: 10.1113/jphysiol.1971.sp009373
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous activity of cerebellar Purkinje cells and their responses to impulses in climbing fibres

Abstract: SUMMARY1. Spontaneous discharges and evoked responses of Purkinje cells have been studied in the anterior lobe vermis of the cerebellum in cats anaesthetized with thiopentone sodium.2. Spontaneous activitywas oftwo kinds: (a) single spikes which occurred in long trains and were discharged at average frequencies of 50-125/sec and (b) burst responses due to climbing fibre (CF) activation of the cell. These occurred at an average frequency close to 1/sec.3. CF responses were evoked by either stimulation of the Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
65
2

Year Published

1973
1973
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 22 publications
9
65
2
Order By: Relevance
“…The over-all pattern of P cell discharge found here, consisting of a rather irregular discharge of simple spikes, punctuated by climbing fibre responses occurring at a mean rate in the region of 1/sec, is qualitatively similar to that found in numerous other investigations. However, the simple spike discharge was somewhat more irregular (as indicated by a larger coefficient of variation of the interspike intervals) and its mean rate (25/sec) was a little slower than has been reported for barbiturate anaesthetized (Bell & Grimm, 1969;Murphy & Sabah, 1970;Latham & Paul, 1971), de-cerebrate (Bloedel & Roberts, 1969;Murphy & Sabah, 1970) or unanaesthetized intact cats (Hobson & McCarley, 1972a, b;Marchesi & Strata, 1971; Armstrong & Rawson, 1976& Rawson, , 1979 and for unanaesthetized monkeys (Thach, 1968(Thach, , 1970Mano, 1970). In the present study, the administration of pentobarbitone temporarily stopped the P cell discharge, which was both slower and more regular when it resumed, as Murphy & Sabah (1970) found in decerebrate preparations.…”
Section: Comparison Of Purkinje Cell and Interpositus Neurone Responsesmentioning
confidence: 88%
“…The over-all pattern of P cell discharge found here, consisting of a rather irregular discharge of simple spikes, punctuated by climbing fibre responses occurring at a mean rate in the region of 1/sec, is qualitatively similar to that found in numerous other investigations. However, the simple spike discharge was somewhat more irregular (as indicated by a larger coefficient of variation of the interspike intervals) and its mean rate (25/sec) was a little slower than has been reported for barbiturate anaesthetized (Bell & Grimm, 1969;Murphy & Sabah, 1970;Latham & Paul, 1971), de-cerebrate (Bloedel & Roberts, 1969;Murphy & Sabah, 1970) or unanaesthetized intact cats (Hobson & McCarley, 1972a, b;Marchesi & Strata, 1971; Armstrong & Rawson, 1976& Rawson, , 1979 and for unanaesthetized monkeys (Thach, 1968(Thach, , 1970Mano, 1970). In the present study, the administration of pentobarbitone temporarily stopped the P cell discharge, which was both slower and more regular when it resumed, as Murphy & Sabah (1970) found in decerebrate preparations.…”
Section: Comparison Of Purkinje Cell and Interpositus Neurone Responsesmentioning
confidence: 88%
“…However, preferential driving by synchronous inputs, as discussed above, could effectively result in the multiplexing of two information channels in the DCN inputs. The complex spike modulates simple spiking of Purkinje cells, e.g., by simple spike pauses after a complex spike (Latham and Paul, 1971;Armstrong and Rawson, 1979), which may in turn elicit rebound firing of DCN neurons (Aizenman and Linden, 1999) (but see Alviña et al, 2008). Synchronous CS activity across Purkinje cells may therefore result in activation of downstream neuronal populations in the DCN, with spatial activation patterns representing information at discrete time points marked out by subthreshold oscillations in the olive.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebellar Purkinje neurons have long been a focus of detailed electrophysiological study. Two striking features of Purkinje neurons in vivo are regular, spontaneous firing (Bell and Grimm, 1969;Latham and Paul, 1971) and, upon stimulation of climbing fibers, formation of "complex spikes" consisting of multiple peaks (Eccles et al, 1966(Eccles et al, ,1967Martinez et al, 1971). Work with in vitro preparations has suggested that both properties may depend, in part, on intrinsic membrane properties of Purkinje neurons.…”
mentioning
confidence: 99%